Data from: Vicariance, long-distance dispersal, and regional extinction–recolonization dynamics explain the disjunct circumpolar distribution of the arctic-alpine plant Silene acaulis - Gussarova, Galina; Allen, Geraldine A.; Mikhaylova, Yulia; McCormick, Laurie J.; Mirré, Virginia; Marr, Kendrick L.; Hebda, Richard J.; Brochmann, Christian (Zenodo, 2015)
PREMISE OF THE STUDY: Many arctic-alpine species have vast geographic ranges, but these may encompass substantial gaps whose origins are poorly understood. Here we address the phylogeographic history of Silene acaulis, a perennial cushion plant with a circumpolar distribution except for a large gap in Siberia. METHODS: We assessed genetic variation in a range-wide sample of 103 populations using plastid DNA (pDNA) sequences and AFLPs (amplified fragment length polymorphisms). We constructed a haplotype network and performed Bayesian phylogenetic analyses based on plastid sequences. We visualized AFLP patterns using principal coordinate analysis, identified genetic groups using the program structure, and estimated genetic diversity and rarity indices by geographic region. KEY RESULTS: The history of the main pDNA lineages was estimated to span several glaciations. AFLP data revealed a distinct division between Beringia/North America and Europe/East Greenland. These two regions shared only one of 17 pDNA haplotypes. Populations on opposite sides of the Siberian range gap (Ural Mountains and Chukotka) were genetically distinct and appear to have resulted from postglacial leading-edge colonizations. We inferred two refugia in North America (Beringia and the southern Rocky Mountains) and two in Europe (central-southern Europe and northern Europe/East Greenland). Patterns in the East Atlantic region suggested transoceanic long-distance dispersal events. CONCLUSIONS: Silene acaulis has a highly dynamic history characterized by vicariance, regional extinction, and recolonization, with persistence in at least four refugia. Long-distance dispersal explains patterns across the Atlantic Ocean, but we found no evidence of dispersal across the Siberian range gap. sa_AFLP_458ind_335char AFLP data matrix (0;1). See description in the readMe file. sa_pDNA_107ind_3190char pDNA sequence file in nexus format. See description in ReadMe file.